PENGGUNAAN METODE ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VI SD NEGERI 38 PADA PEMBELAJARAN IPS TENTANG DAMPAK GLOBALISASI - Ishak Said (Universitas Muhammadiyah Bangka Belitung, 2023)
ABSTRACT The background of the problem in this class action research is that students have not been active because the teacher still uses conventional methods in the form of lectures, so that the social studies learning outcomes of grade VI students of SD Negeri 38 Pangkalpinang have not yet reached the optimal completeness value. The problem is formulated as follows: